2020
DOI: 10.1096/fj.201902368rr
|View full text |Cite
|
Sign up to set email alerts
|

FAM3A plays crucial roles in controlling PDX1 and insulin expressions in pancreatic beta cells

Abstract: So far, the mechanism that links mitochondrial dysfunction to PDX1 inhibition in the pathogenesis of pancreatic β cell dysfunction under diabetic condition remains largely unclear. This study determined the role of mitochondrial protein FAM3A in regulating PDX1 expression in pancreatic β cells using gain‐ and loss‐of function methods in vitro and in vivo. Within pancreas, FAM3A is highly expressed in β, α, δ, and pp cells of islets. Islet FAM3A expression was correlated with insulin expression under physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 74 publications
(176 reference statements)
3
10
0
Order By: Relevance
“…FAM3A is a cytokine that is ubiquitously expressed in the tissues of human and rodents [ 14 ]. FAM3A controls the expression of pancreas/duodenum homeobox protein 1 (PDX1) and insulin and insulin secretion in the pancreatic beta cells under physiologica l and diabetic conditions [ 35 ]. Zhou et al [ 36 ] reported that the expression of FAM3A in human hepatocytes is increased by the PPARγ agonist, but not by PPARα and PPARδ agonists.…”
Section: Discussionmentioning
confidence: 99%
“…FAM3A is a cytokine that is ubiquitously expressed in the tissues of human and rodents [ 14 ]. FAM3A controls the expression of pancreas/duodenum homeobox protein 1 (PDX1) and insulin and insulin secretion in the pancreatic beta cells under physiologica l and diabetic conditions [ 35 ]. Zhou et al [ 36 ] reported that the expression of FAM3A in human hepatocytes is increased by the PPARγ agonist, but not by PPARα and PPARδ agonists.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously 24 , mice were anesthetized, and the upper part of the common bile duct near the hepatic portal vein was isolated and ligated. The duodenum was pulled with forceps and perfused with 3–5 mL of collagenase V [Sigma, 0.5 mg/mL in Hank’s Balanced Salt Solution (HBSS)] in the lower part of the common bile duct using an injection syringe.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we also showed that insulin secretion is significantly impaired in pancreatic β cell-specific knockout FAM3A mice. Mechanistically, FAM3A-induced ATP release activates the CaM-forkhead box protein A2 (FOXA2) pathway to directly induce the expression of pancreatic-duodenal homeobox 1 (PDX1), the key regulator of insulin gene expression, and β-cell growth and proliferation 24 . However, the role of intracellular ATP in FAM3A-induced PDX1 expression and insulin secretion remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , FAM3A overexpression enhances whereas FAM3A deficiency blunts ATP production and secretion, and GSIS in primary islets and β cell lines ( Yang et al, 2020 ; Yan et al, 2021 ). Mechanistically, FAM3A-promoted ATP release activates both P2X and P2Y receptors to increase cellular Ca 2+ , which stimulates the translocation of calmodulin (CaM) from cytoplasm into nucleus and directly interacts with forkhead box protein A2 (FOXA2) to augment its activation effect on the PDX-1 gene expression ( Yang et al, 2020 ). Upregulation of PDX-1 finally induces insulin gene expression and insulin secretion ( Yang et al, 2020 ).…”
Section: Atp Regulates Islet β Cell Functionsmentioning
confidence: 99%
“…Mechanistically, FAM3A-promoted ATP release activates both P2X and P2Y receptors to increase cellular Ca 2+ , which stimulates the translocation of calmodulin (CaM) from cytoplasm into nucleus and directly interacts with forkhead box protein A2 (FOXA2) to augment its activation effect on the PDX-1 gene expression ( Yang et al, 2020 ). Upregulation of PDX-1 finally induces insulin gene expression and insulin secretion ( Yang et al, 2020 ). Beyond extracellular ATP, intracellular ATP also contributed to FAM3A-induced PDX-1 upregulation and pancreatic β cell proliferation ( Yan et al, 2021 ).…”
Section: Atp Regulates Islet β Cell Functionsmentioning
confidence: 99%